2020
DOI: 10.1249/mss.0000000000002533
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fire Academy Training and Probationary Firefighter Status on Select Basic Health and Fitness Measurements

Abstract: Purpose This study aimed to investigate changes in firefighter recruits’ select health and fitness measurements, from academy training to the early probationary firefighter period. Methods Firefighter recruits from two New England fire academies were followed up prospectively from enrollment at the academy to graduation after 15- to 16-wk training programs, and then for an average of 8 months as probationary firefighters. The participants’ demographic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(56 citation statements)
references
References 36 publications
6
44
1
Order By: Relevance
“…The reviewed studies referred to TP/PO [ 13 , 28 , 30 , 32 ], firefighters [ 15 , 18 , 20 , 22 , 26 , 31 , 34 ], military [ 23 , 33 ], and cadets/recruits (police [ 3 , 16 , 19 , 21 , 25 ], firefighters [ 24 , 27 , 29 ] and military [ 14 , 17 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The reviewed studies referred to TP/PO [ 13 , 28 , 30 , 32 ], firefighters [ 15 , 18 , 20 , 22 , 26 , 31 , 34 ], military [ 23 , 33 ], and cadets/recruits (police [ 3 , 16 , 19 , 21 , 25 ], firefighters [ 24 , 27 , 29 ] and military [ 14 , 17 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Our study is a secondary analysis of a larger clinical trial among a small sample of overweight Caucasian male career firefighters, so the generalizability of our findings is restricted. However, our sample was representative of the United States firefighting population as 96% are male [ 60 ] and >70% are overweight or obese [ 1 ]. We used a maximal GEST to simulate firefighting demands, which does not adequately replicate the extreme physical and mental demands of the job.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the threshold for overweight classification is adjusted upward to !27.5 kg m À2 as suggested previously, 13,22 the firefighters would first exceed this threshold in their mid-twenties and the mean BMI for firefighter recruits appears to be close to this threshold as well. 48,49 Another longitudinal study demonstrated that firefighter's BMI increased by 0.14 kg m À2 with each 1-year increase of follow-up 37 while a repeated measures study found that firefighters BMI increase 0.80 kg m À2 between two observations 5-years apart. 18 For comparison, the slope of the mixed models for BMI in the present study suggests that firefighter's body mass would increase 0.66 kg m À2 over 5 years.…”
Section: Discussionmentioning
confidence: 99%